Development and Psychometric Evaluation of the HPV Clinical Trial Survey for Parents (CTSP‐HPV) Using Traditional Survey Development Methods and Community Engagement Principles. Issue 6 (4th November 2015) - Cunningham, Jennifer; Wallston, Kenneth A.; Wilkins, Consuelo H.; Hull, Pamela C.; Miller, Stephania T.
Abstract: Objective: This study describes the development and psychometric evaluation of HPV Clinical Trial Survey for Parents with Children Aged 9 to 15 (CTSP‐HPV) using traditional instrument development methods and community engagement principles. Methods: An expert panel and parental input informed survey content and parents recommended study design changes (e.g., flyer wording). A convenience sample of 256 parents completed the final survey measuring parental willingness to consent to HPV clinical trial (CT) participation and other factors hypothesized to influence willingness (e.g., HPV vaccine benefits). Cronbach's a, Spearman correlations, and multiple linear regression were used to estimate internal consistency, convergent and discriminant validity, and predictively validity, respectively. Results: Internal reliability was confirmed for all scales ( a ≥ 0.70.). Parental willingness was positively associated ( p < 0.05) with trust in medical researchers, adolescent CT knowledge, HPV vaccine benefits, advantages of adolescent CTs ( r range 0.33–0.42), supporting convergent validity. Moderate discriminant construct validity was also demonstrated. Regression results indicate reasonable predictive validity with the six scales accounting for 31% of the variance in parents' willingness. Conclusions: This instrument can inform interventions based on factors that influence parental willingness, which may lead to the eventual increase in trial participation. Further psychometric testing is warranted.